Реалізація цифрових фільтрів на мікроконтролерах STM32 з використанням кільцевих буферів - Зубков, О. В.; Яковенко, О. С. (ХНУРЕ, 2023)
The analysis of digital filters in electronics and their software implementation on general-purpose microcontrollers was completed in this work. A real-time digital filtering algorithm has been developed for STM32 microcontrollers with support for DSP instructions and the use of ring buffers. A study of the proposed algorithm performance was carried out using the example a digital low-pass filter with a finite impulse response implementation. A comparative analysis of performance measurement results and comparisons with the results of using the standard library proved the effectiveness of the proposed algorithm.
Keywords: цифровий фільтр; мікроконтролер; буфер